Physical Activity and Sports Practice in Improving Body Composition and Sustainable Health - Georgian, Badicu; Campa, Francesco (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In this book, distinguished contributors, including anthropologists, human biologists, physiologists, nutritionists, and clinical scientists, describe many of the new strategies for assessing body composition and physical performance. This volume is suitable for students and professionals in sports nutrition and exercise. It provides a needed link between body composition and physical performance. It will also be useful to workers in sports medicine and ergonomics.